Delineating the role of negative verbal thinking in promoting worry, perceived threat, and anxiety - Hirsch, C.; Perman, G.; Hayes, Sarra; Eagleson, C.; Mathews, A. (2015)
Worry is characterized by streams of verbal thoughts about potential negative outcomes. Individuals with high levels of worry (and particularly those with generalized anxiety disorder) find it very difficult to control worry once it has started. What is not clear is the extent to which verbal negative thinking style maintains worry. Our study aimed to disentangle the effects of verbal versus imagery based thinking, and negative versus positive worry-related content on subsequent negative intrusive thoughts. High worriers were trained to engage in imagery or verbal processing, focusing on either negative or positive outcomes of their current main worry. Both thinking style and valence of worry content influenced later negative intrusive thoughts that play a role in initiating worry episodes. In contrast, only valence influenced subjective ratings of worry outcomes (i.e., cost, concern, and ability to cope, although not probability), with positive valence leading to lower ratings, irrespective of thinking style.